Online political hate speech in Europe : the rise of new extremisms - Ziccardi, Giovanni (Edward Elgar Publishing, 2020)
"This timely book addresses the increasingly widespread issue of online political hatred in Europe. Taking an interdisciplinary approach, it examines both the contributions of new technologies, in particular social networks, to the rise of this phenomenon, and the legal and political contexts in which it is taking place. Through an analysis of online hate speech and its impacts, Giovanni Ziccardi characterizes contemporary political hatred in Europe, highlighting its victims, communication strategies, and the creation of a cross-national network of extremists enabled by technology. He compares legal and political responses to the problem at both national and EU levels, as well as the approach taken by the US, in order to examine the effectiveness of current measures. Finally, he evaluates possible remedies for the situation, including both legal and technological solutions, and outlines the potential for a unified European framework to counter the spread of hatred online. Online Political Hate Speech in Europe will be an essential read for scholars and students in law and politics looking for an in-depth analysis of this issue. It will also be useful for politicians, policy makers and practitioners seeking to understand the mechanisms underlying the circulation of political hatred"--